Computer Vision-Based Approach for Quantifying Occupational Therapists' Qualitative Evaluations of Postural Control. (27th April 2020) - Hagihara, Hiromichi; Ienaga, Naoto; Enomoto, Daiki; Takahata, Shuhei; Ishihara, Hiroyuki; Noda, Haruka; Tsuda, Koji; Terayama, Kei
Abstract : This study aimed to leverage computer vision (CV) technology to develop a technique for quantifying postural control. A conventional quantitative index, occupational therapists' qualitative clinical evaluations, and CV-based quantitative indices using an image analysis algorithm were applied to evaluate the postural control of 34 typically developed preschoolers. The effectiveness of the CV-based indices was investigated relative to current methods to explore the clinical applicability of the proposed method. The capacity of the CV-based indices to reflect therapists' qualitative evaluations was confirmed. Furthermore, compared to the conventional quantitative index, the CV-based indices provided more detailed quantitative information with lower costs. CV-based evaluations enable therapists to quantify details of motor performance that are currently observed qualitatively. The development of such precise quantification methods will improve the science and practice of occupational therapy and allow therapists to perform to their full potential.